A trial of arbidol hydrochloride in adults with COVID-19. Issue 13 (5th July 2022) - Zhao, Jingya; Zhang, Jinnong; Jin, Yang; Tang, Zhouping; Hu, Ke; Sun, Hui; Shi, Mengmeng; Yang, Qingyuan; Gu, Peiyu; Guo, Hongrong; Li, Qi; Zhang, Haiying; et al.
Abstract: Background: To date, there is no effective medicine to treat coronavirus disease 2019 (COVID-19), and the antiviral efficacy of arbidol in the treatment for COVID-19 remained equivocal and controversial. The purpose of this study was to evaluate the efficacy and safety of arbidol tablets in the treatment of COVID-19. Methods: This was a prospective, open-label, controlled and multicenter investigator-initiated trial involving adult patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Patients were stratified 1:2 to either standard-of-care (SOC) or SOC plus arbidol tablets (oral administration of 200 mg per time, three times a day for 14 days). The primary endpoint was negative conversion of SARS-CoV-2 within the first week. The rates and 95% confidential intervals were calculated for each variable. Results: A total of 99 patients with laboratory-confirmed SARS-CoV-2 infection were enrolled; 66 were assigned to the SOC plus arbidol tablets group, and 33 to the SOC group. The negative conversion rate of SARS-CoV-2 within the first week in patients receiving arbidol tablets was significantly higher than that of the SOC group (70.3% [45/64] vs . 42.4% [14/33]; difference of conversion rate 27.9%; 95% confidence interval [CI], 7.7%–48.1%; P   =  0.008). Compared to those in the SOC group, patients receiving arbidol tablets had a shorter duration of clinical recovery (median 7.0 days vs . 12.0 days; hazard ratio [HR]: 1.877, 95% CI: 1.151–3.060, P  = 0.006), symptom of fever (median 3.0 days vs . 12.0 days; HR: 18.990, 95% CI: 5.350–67.410, P  < 0.001), as well as hospitalization (median 12.5 days vs . 20.0 days; P  < 0.001). Moreover, the addition of arbidol tablets to SOC led to more rapid normalization of declined blood lymphocytes (median 10.0 days vs . 14.5 days; P  > 0.05). The most common adverse event in the arbidol tablets group was the elevation of transaminase (5/200, 2.5%), and no one withdrew from the study due to adverse events or disease progression. Conclusions: SOC plus arbidol tablets significantly increase the negative conversion rate of SARS-CoV-2 within the first week and accelerate the recovery of COVID-19 patients. During the treatment with arbidol tablets, we find no significant serious adverse events. Trial registration: Chinese Clinical Trial Registry, NCT04260594, www.clinicaltrials.gov/ct2/show/NCT04260594?term=NCT04260594&draw=2&rank=1